Facilitating innovation in European research area through pre-competitive EU-funded COST Actions - Ruslan Rakhmatullin; Louis Rennan (Journal of Innovation and Entrepreneurship, 2014)
The European Union (EU) Heads of States regularly confirm that knowledge and innovation are critical to Europe's growth and agreed to make the EU the most competitive knowledge-driven economy. The EU's ability to facilitate innovation by strengthening its research capacities is central to achieving this goal. Some EU initiatives under this innovation policy integrate research capacities already existing in individual states through pan-European participation in collaborative projects in science and technology. The EU is financing a number of formal pre-competitive networking programs aiming at a better deployment of existing national research capacities via their inclusion in joint research initiatives. Although there is a general consensus that increasing levels of collaboration amongst researchers produce better results, the issue of research networking and of related research outcomes continues to generate debate with a wide variety of views on what roles such programs play and their general implications for research and scientific performance. As the EU Framework Programme 7 is coming to its end, this paper explores whether such formal networking programs contribute to facilitating innovation in the European Research Area by enabling Science and Technology participants to achieve anticipated research outcomes from their involvement in such programs.
Keywords: 650; Innovation; Collaboration; COST Action; Science and technology; Framework Programme 7; Pre-competitive; Formal networking programs